Comparison of the Effects of Thoracic Epidural Anesthesia with General Anesthesia on Hemodynamic Changes and its Complications in Patients Undergoing Laparoscopic Cholecystectomy - Mohammad Azad Majedi (Advanced Biomedical Research, 2019)
Background: Epidural anesthesia (EA) today has been used extensively in surgical procedures and the management of pain associated with midwifery and chronic pain. This type of anesthesia can be done in different technical, physiological, and pharmacological ways. The aim of this study was to compare the effects of thoracic EA with general anesthesia (GA) on hemodynamic changes and its complications in patients underwent laparoscopic colonoscopy. Materials and Methods: This clinical trial study was conducted on 80 patients undergoing laparoscopic cholecystectomy with EA or GA based on inclusion and exclusion criteria. The patients were randomly divided into two groups of 40 and changes in blood pressure, systolic blood pressure (SBP) and diastolic blood pressure (DBP), heart rate (HR), and arterial blood oxygen saturation were measured. The incidence of nausea, vomiting, chills, and itching in the two groups was recorded. The analysis was performed descriptively and also using t-test and Chi-square tests. Results: The results showed that the mean of SBP and DBP, HR, and arterial blood oxygen saturation and the incidence of nausea and vomiting was statistically significant (P < 0.05) between the two groups at 4, 6, and 12 h after anesthesia and it was higher in a group of GA. There was no significant difference in shivering and itching between the two groups (P > 0.05). Conclusion: The results of this study indicated that thoracic EA in patients with laparoscopic cholecystectomy has significant effects on factors such as SBP and DBP and arterial blood oxygen saturation. Furthermore, EA has fewer complications than GA, and it is the preferable approach